A six axis load cell for the analysis of the dynamic impact response of a hybrid III dummy. (August 2016) - Ballo, F.; Gobbi, M.; Mastinu, G.; Previati, G.
Abstract: An innovative six axis load cell is presented and employed for frontal impact tests on a Hybrid III 50th percentile dummy. The new six axis load cell, designed at Politecnico di Milano (Technical University of Milan), is a quasi-statically determined structure consisting of a central three spoke element fixed to an external frame by means of special joints appositely designed to minimize friction. A specifically designed electronic board is embedded in the load cell and allows real-time signal processing. The developed load cell has been employed during frontal impact tests on a Hybrid III dummy. An impact force is applied to the dummy's head by means of an impact pendulum. The accelerations in two different points of the dummy's head as well the impact force have been measured. A simple 1 DOF analytical model of the head and neck has been developed. Neck stiffness and damping have been identified directly from experimental data.